(18)F-4V for PET-CT imaging of VCAM-1 expression in inflammatory atherosclerosis - Nahrendorf, Matthias (2009)
OBJECTIVES: To iteratively develope and validate an (18)F labeled small molecule VCAM-1 affinity ligand and demonstrate the feasibility of imaging VCAM-1 expression by PET-CT in murine arteries. BACKGROUND: Hybrid PET-CT imaging may allow simultaneous assessment of atherosclerotic lesion morphology (CT) and biology through the development of novel tracers (PET), thus facilitating early risk assessment in individual patients. METHODS: A cyclic, a linear, and an oligomer affinity peptide, internalized into endothelial cells by VCAM-1–mediated binding, were initially derivatized with DOTA to determine their binding profiles and pharmacokinetics. The lead compound was then (18)F labeled and tested in apoE(−/−) mice as well as models of MI and heart transplant rejection. RESULTS: The tetrameric peptide had the highest affinity and specificity for VCAM-1 (97% inhibition with soluble VCAM-1). In vivo PET-CT imaging using (18)F-4V showed 0.31±0.02 SUV in murine atheroma (ex vivo %IDGT 5.9±1.5). (18)F-4V uptake colocalized with atherosclerotic plaques on Oil Red O staining, and correlated to mRNA levels of VCAM-1 measured by quantitative RT-PCR (R=0.79, p=0.03). Mice treated with atorvastatin had significantly lower lesional uptake (p<0.05). Furthermore, (18)F-4V imaging in myocardial ischemia and in transplanted hearts showed good correlation with ex vivo measurement of VCAM-1 mRNA. CONCLUSION: (18)F-4V allows noninvasive PET-CT imaging of VCAM-1 in inflammatory atherosclerosis, has the dynamic range to quantify treatment effects and correlates with inflammatory gene expression.